How do National Health Service (NHS) organisations respond to patient concerns? A qualitative interview study of the Patient Advice and Liaison Service (PALS) - Shepard, K; Buivydaite, R; Vincent, C (BMJ Publishing Group, 2021)
Objectives To describe the current work of the Patient Advice and Liaison Service (PALS) and assess the service’s potential to resolve concerns and contribute to organisational learning. Design A qualitative study using semistructured interviews. Setting Four mental health trusts and four acute trusts in the English National Health Service, a total of eight PALS across different trusts. Participants Twenty-four participants comprising of PALS staff and clinicians working with PALS teams. Methods Semistructured interviews were undertaken with participants using video conferencing software. The framework method was used for the analysis of the large qualitative dataset, which is a conventional method of analysis, similar to thematic or qualitative content analysis. Results PALS teams fulfil their core responsibilities by acting as point of contact for patients, providing information and resolving a variety of recurrent problems, including PALS staff communication, staff attitudes and waiting times. The remit and responsibilities of each PALS has often broadened over time. Barriers to resolving concerns included a lack of awareness of PALS, limited to no policies informing how staff resolve concerns, an emphasis on complaints and the attitude of clinical staff. Senior management had widely differing views on how the PALS should operate and the management of complaints is a much higher priority. Few PALS teams carried out any analysis of the data or shared data within their organisations. Conclusions PALS teams fulfil their core responsibilities by acting as point of contact for patients, providing information and resolving concerns. PALS staff also act as navigators of services, mediators between families and staff and, occasionally, patient advocates in supporting them to raise concerns. PALS has the potential to reduce complaints, increase patient satisfaction and provide rapid organisational feedback. Achieving this potential will require more awareness and support within organisations together with updated national policy guidance.